Gamification in higher education: a self-determination theory perspective on the reward system - Marinensi, Giada; Botte, Brunella; Romero Carbonell, Marc (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
Educational gamification is a rising area, and several studies have already been conducted in the context of Higher Education, with encouraging results, especially about the effectiveness of gamification in increasing students perceived motivation to learn. The authors of this study explore how game elements commonly used in gamified learning systems, such as badges, points, progression bars and levels, can affect students motivation by fulfilling their needs for competence, relatedness, and autonomy, in the framework of the self-determination theory (SDT). The final goal is to better understand how to build the reward system of an educational gamified application aimed at maximising students motivation.